Attitudinal Factors Influencing Digital Collaborative Consumption Among Internet Users: A Confirmatory Study in Indonesia - Ahmad, Lukni Burhanuddin; Arnita, Devi; Nasution, Reza Ashari (Gadjah Mada International Journal of Business, 2025)
There has been a substantial surge in people participating in collaborative consumption (CC) over the past few years, particularly on digital platforms. This phenomenon has encouraged some researchers to explore the motivational factors affecting user intention to use CC. However, the previous research has predominantly concentrated on identifying these factors in the context of CC service, with limited attention specifying the digital platform where the interaction among users is different. Hwang and Griffiths's model of intention that predicts the behavioral intention of millennials' participation in CC is unique in a way that it recognizes both attitude and empathy as the main factors affecting intention to use a CC platform. The model could be relevant for CC, as it covers different values such as utilitarian, hedonic, and symbolic values. This study has developed a model to make it comprehensive by adding several factors from past research: perceived behavioral control and online initial trust. We tested the model in the Indonesian context using partial least squares regression. One of the world’s most populous countries, In- donesia provides a thought-provoking digital CC practice opportunity. The results show that empathy and online initial trust are not significant predictors of intention to partic- ipate in CC. In addition, utilitarian value is not a significant predictor of attitude toward participating in CC. Thus, attitude is the critical factor affecting intention to participate in CC, and perceived usefulness, perceived ease of use, and hedonic and symbolic values are significant predictors of the effect of attitude on participation in CC. This study can provide valuable insight for those startup practitioners who create this type of business model, characterized by its rapid change and volatile nature. The results could play a role in guiding marketers specializing in CC to enhance their apps using effective tactics or strategies, thereby improving the customer’s participation on their platform